SISTEM INFORMASI EVALUASI KINERJA AKADEMIK DI UNIVERSITAS PAPUA: PERFORMANCE EVALUATION INFORMATION SYSTEM ACADEMIC AT PAPUA UNIVERSITY - Fridolin F Paiki; Nurdiana Malasari (Universitas Papua, 2018)
The University of Papua in the performance evaluation process still uses the automatic system manuals. The manual performance evaluation process is less reliable because it is still experienced various problems, including limited human resources in processing data, data collection techniques are done manually with distributing questionnaires requires a lot of document files as well need a long time. The existence of these problems, then made a plan Information System for the Evaluation of Academic Community Performance at the University of Papua. Expected This performance evaluation system can help overcome problems in the process collection and processing of data related to the assessment process performance. This performance evaluation system uses the Panada framework, PHP My Admin, MySQL as the database and Xampp as the offline server, and designed with simple flow and interface design so that it can be done easily used.